INTERNATIONAL JUSTICE COURT, ROLE AND DIRECTIONS OF ACTIVITY OF THE EUROPEAN JUSTICE COURT IN THE SETTLEMENT OF DISPUTED LAWS - Габибова, Кенуль Абюльфаз гызы (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: determination of the basic functions of the courts operating in the world and the European Union and the establishment of the features of the International Court of Justice, the European Court of Justice and the International Criminal Court. Methods: comparison, analysis, synthesis and historical method. Results: it was established that the International Court of Justice, the European Court of Justice and the International Criminal Court differ not only in their territorial jurisdiction. In particular, the fact that lawyers in the European Court, along with judges, can also be considered a separate administrative position, have the authority to give reviews (despite the fact that these reviews are not mandatory), and significantly influence it, distinguishes it from other courts and is very an interesting feature that can be of practical importance, including for the Republic of Azerbaijan. Legal proceedings are an independent branch of the state and a multifaceted, specific area in which the leading role is determined by the courts. However, national legal proceedings are not always effective, and therefore there is an urgent need for legal proceedings according to basic European and international standards, especially in disputes between states or the qualification of actions of some states. The judiciary is a fundamental segment of justice dominated by the rule of law. The author concludes that although the names of the International Court of Justice and the Court of Justice of the European Union are similar, on the basis of the foregoing, one can witness that both in the cases before them, and in terms of their powers and composition, they differ significantly from each other.